A new species and two new records of Dimini click beetles (Coleoptera: Elateridae) from Xizang, China - Qiu, Lu; Ruan, Yong-Ying (Zootaxa, 2026)
A new species of Dimini, Pseudocsikia xiaobini sp. nov., is described from Mêdog, Xizang, China. It resembles the type species of the genus Pseudocsikia rustica Schimmel & Platia, 1991 in its small body size, reduced hind wings, and large yellow spots on the distal portion of elytra, but differs in brown antennae, longer pronotal hind angles, an M-shaped notch near each of the pronotal hind angles, sparser pronotal punctation, more elongate elytra, and a quadrate expansion of the metacoxal plate. Penia foveolata Schimmel, 1998 and Penia imprimosa Schimmel, 2001 are newly recorded from China (Xizang), and the former is transferred to genus Megapenia Qiu, Ruan, Prosvirov & Kundrata, 2025: Megapenia foveolata (Schimmel, 1998) comb. nov. Habitus and diagnostic characters of all three species are illustrated, and a checklist and key to the Dimini of Xizang are provided. Additionally, the issues concerning the relationship between Paracsikia Schimmel & Platia and Pseudocsikia Schimmel & Platia have also been discussed.